Entrepreneurial ecosystems: founding figures and research frontiers in economic geography - Schäfer, Susann; Mayer, Heike (Zeitschrift für Wirtschaftsgeographie, 2019)
The editorial for the special issue on entrepreneurial ecosystems summarizes the ongoing debate on the entrepreneurial ecosystem concept and portrays the backgrounds of founding figures of the concept. It traces the unique contribution of this issue with regard to recently published research. The contributions deal with the measurement of and the role of specific actors and institutions in entrepreneurial ecosystems.
Gesehen am 27.01.2025